Convergence of Industrial Risk Prevention and Cybersecurity Governance: A Multi-Dimensional Policy Framework for Systemic Resilience and Compliance - Dr. Julian Thorne (Emerging Frontiers Library for The American Journal of Engineering and Technology, 2025)
This research article explores the critical intersections between industrial risk prevention and modern cybersecurity governance, arguing that the silos separating physical safety from digital security are increasingly obsolete in the face of systemic global threats. By examining the regulatory evolution following catastrophic industrial events-specifically the Lubrizol factory fire in France-and the surge in complex cybercrimes such as the Salt Typhoon and Medibank hacks, the study identifies a pervasive gap in integrated risk frameworks. The research synthesizes the French "major risk prevention" approach with international IT audit frameworks (ITAF) and strategic cybersecurity compliance models. It utilizes a comparative analysis of risk policy tools in Normandy, Piedmont, and Victoria to demonstrate that current methodologies remain overly hazards-focused rather than vulnerabilities-focused. Furthermore, the study investigates the role of third-party vendor risks and the necessity of multi-factor authentication (MFA) as fundamental pillars of organizational resilience. By proposing a "Strategic Cybersecurity Governance" model, this article provides a roadmap for aligning technological protection with legal compliance. The findings suggest that systemic resilience requires a shift from reactive post-accident regulation toward proactive, blockchain-enhanced financial privacy and comprehensive auditing strategies. This article contributes a deep theoretical elaboration on the "chronic crisis" of industrial safety and the emerging challenges of cyber-physical integration, providing a publication-ready synthesis for researchers and policymakers.